White matter hyperintensities in diverse populations: A systematic review of literature in the United States - Farkhondeh, Vista; DeCarli, Charles (Cerebral circulation - cognition and behavior, 2024)
•This is the first systematic review to investigate scientific literature studying prevalence of WMH in diverse ethno-racial groups in the US.•23 unique articles met criteria for review, consisting of 16 diverse study cohorts.•The clinical impact of WMH on diverse ethno-racial groups remains unclear, though there is considerable evidence to suggest greater vascular burden on African Americans.•The findings of this review reveal a knowledge gap indicating a need for standardizing research of cognitive health in relation to WMH amongst diverse populations. As the United States’ (US) elderly population becomes increasingly diverse, it is imperative that research studies address cognitive health in diverse populations of older Americans. White Matter Hyperintensities (WMH) are useful imaging findings that can be studied in elderly individuals and have been linked to an increased risk of neurological conditions, such as stroke, cognitive impairment, and dementia. We performed a systematic review of literature using PubMed sources to compile all the studies that investigated the prevalence of ethnic and racial differences of WMH burden amongst diverse groups in the US. We identified 23 unique articles that utilized 16 distinct cohorts of which 94 % were prospective, longitudinal studies that included community-based and family-based populations. The overall results were heterogenous in all aspects of data collection and analysis, limiting our ability to run meta-analyses and draw definitive conclusions. General observations suggest increased vascular risk on African American populations, contributing to greater WMH burden in that population. Overall, the findings of this study indicate a need for a standardized approach to investigating WMH in efforts to measure its clinical impact on diverse populations.